1988
DOI: 10.1084/jem.167.3.752
|View full text |Cite
|
Sign up to set email alerts
|

Toxic shock syndrome toxin 1 as an inducer of human tumor necrosis factors and gamma interferon.

Abstract: We present evidence that toxic shock syndrome toxin 1 (TSST-1) induces the production of high levels of TNF by human blood monocytes. Enriched lymphocyte preparations incubated with the staphylococcal toxin produced significant levels of TNF-like activity that is not neutralized by anti-rHuTNF antibodies and is likely to be lymphotoxin (LT or TNF-beta). We demonstrate also that TSST-1 is a potent inducer of IFN-gamma. When lymphocyte preparations were costimulated with PMA, the TSST-1 effect was strongly poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(109 citation statements)
references
References 30 publications
3
105
0
1
Order By: Relevance
“…Recently two groups reported the production of TNF by human blood MNCs [28,29] by using the L929 cytotoxicity assay. Our results extend these studies by showing that TSST-1 induces TNF, IL-1 a, and IL-1 (3 from MNCs, as determined by specific RIAs.…”
Section: Lps (Ng/ml)mentioning
confidence: 99%
“…Recently two groups reported the production of TNF by human blood MNCs [28,29] by using the L929 cytotoxicity assay. Our results extend these studies by showing that TSST-1 induces TNF, IL-1 a, and IL-1 (3 from MNCs, as determined by specific RIAs.…”
Section: Lps (Ng/ml)mentioning
confidence: 99%
“…Their interactions with cells of the immune system initiate a massive production of the proinflammatory cytokines, tumor-necrosis factor ␣ (TNF-␣), interferon-␥ (IFN-␥), and interleukin-1 (IL-1). Both the hyperactivation of T cells and the excessive production of proinflammatory cytokines are responsible for the pathogenesis of toxic shock and various autoimmune disorders [2][3][4][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that HLA class IP cells eould be killed by T cells reactive to SEs through the interaction among TCR, exotoxins and class II moleeules [II]. Tumour necrosis faetor-bcta induced by TSST-1 [29] could also be harmful to VEC. The consecutive chains of these biological reactions would result in the development of vaseulitis.…”
Section: Discussionmentioning
confidence: 99%